2000
DOI: 10.1074/jbc.275.17.12581
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state and Transient Kinetics of Escherichia coli Nitric-oxide Dioxygenase (Flavohemoglobin)

Abstract: The flavoHbs 1 belong to a 1.8 billion-year-old family of globin molecules that includes O 2 -binding Hbs and Mbs isolated from animals, plants, fungi, protozoa, bacteria, and worms (1-6). FlavoHbs have a unique two-domain structure containing linked Hb and reductase domains with extensive homology to the mammalian Hbs and metHb reductases (1, 7). Other Hbs appear to be co-expressed with associated metHb reductases (8). An O 2 transport or storage function, like that of the erythrocytic Hbs and muscle Mbs, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
169
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(191 citation statements)
references
References 58 publications
21
169
1
Order By: Relevance
“…The Fe III NO dissociation rates of mammalian NOS enzymes are within a range that is typical for other ferric heme proteins, whereas in bsNOS this rate is near the lower end of the range (Table V). In contrast, the rates of ferric heme reduction in mammalian NOS enzymes range between 0.1 and 4 s Ϫ1 at 10°C, which are much slower than in other heme enzymes that contain attached flavin domains like cytochrome P450BM3 (23) or flavohemoglobin (24). We suspect that this circumstance evolved in the mammalian NOS to enable their NO release from the heme.…”
Section: Discussionmentioning
confidence: 67%
“…The Fe III NO dissociation rates of mammalian NOS enzymes are within a range that is typical for other ferric heme proteins, whereas in bsNOS this rate is near the lower end of the range (Table V). In contrast, the rates of ferric heme reduction in mammalian NOS enzymes range between 0.1 and 4 s Ϫ1 at 10°C, which are much slower than in other heme enzymes that contain attached flavin domains like cytochrome P450BM3 (23) or flavohemoglobin (24). We suspect that this circumstance evolved in the mammalian NOS to enable their NO release from the heme.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, given the in vivo localization of ns-Hbs in metabolically active tissues and the very high affi nity for oxygen binding of several r-ns-Hbs, it is unlikely that they function as oxygen scavengers (Arredondo-Peter et al 1998, Hill 1998). Both Arredondo-Peter et al (1998) and Hill (1998) have suggested that plant ns-Hbs could act as NO scavengers, in a similar manner to those of the bacterial fl avohemoglobins, which have been documented to possess nitric oxide dioxygenase properties (R Gardner et al 1998, A. Gardner 2000. However, nsHbs lack a fl avin domain, which would be required for functioning as an NO dioxygenase.…”
Section: Discussionmentioning
confidence: 97%
“…The decreased viability of the J96∆norV mutant may indicate that the oxygen level in the static culture in our experiments is microaerobic rather than aerobic. In hypoxic conditions the dioxygenase activity of Hmp have been shown to be reduced [42], which may explain why Hmp was unable to compensate for the norV-deficiency. Taken together, our results suggest that, under the experimental conditions used, both Hmp and NorV seem to be important for NO protection in UPEC.…”
Section: Discussionmentioning
confidence: 99%